Pengaruh Kemampuan Komunikasi Pengajar Sekolah Menengah Atas (SMA) Dalam Meningkatkan Mutu Hasil Belajar Di Kabupaten Majene - Zulfikar Haswin (Al-MUNZIR, 2020)
This research aims to find out the influence between communication skills of Senior High School Teachers (SMA) in improving student learning outcomes in Majene Regency. This research uses descriptive quantitative method using an instrument that is a questionnaire (written question) sourced from teaching staff at the Senior High School Level in the Majene Regency Area to obtain primary data. Secondary data in this study were obtained from the results of field documentation by researchers. The results showed that the improvement in communication skills of teachers is in line with the increase in the quality of student learning outcomes and has a close significance relationship between the two. Thus, the higher the Knowledge, Skill, and Motivation components of teacher communication skills will be directly proportional to the quality of student learning outcomes and have a positive and strong influence.